Integrative taxonomy reveals a new species of Leptobrachella (Anura: Megophryidae) from the mountains of northern Thailand - Chen, Jin-Min; Suwannapoom, Chatmongkon; Wu, Yun-He; Poyarkov, Nikolay A.; Xu, Kai; Pawangkhanant, Parinya; Che, Jing (Zootaxa, 2021)
The genus Leptobrachella is one of the most speciose and taxonomically troubling groups of Asian anurans. Herein, we describe a new species of Leptobrachella from Doi Inthanon, Chiang Mai Province, Thailand based on the integration of morphological, acoustic and molecular data. The new species, Leptobrachella murphyi sp. nov., is morphologically distinguished from its congeners on the basis of body size, dorsal skin texture and coloration, ventral coloration and pattern, degree of webbing and fringing on the fingers and toes, iris coloration in life, pattern of markings on flanks and pattern of body macroglands. It also differs from its phylogenetically close congeners by an uncorrected p-distance of >9.6% for a fragment of 16S rRNA. The advertisement call of the new species consists of 4.5–4.7 kHz (at 15 °C) and without a distinct introductory note. Leptobrachella murphyi sp. nov. likely occurs across the Thanon Thong Chai Range and analyses provide evidence of unknown biodiversity and species composition on Doi (mountain) Inthanon. In addition, the congeneric species L. minima was also confirmed in Doi Inthanon. The coexistence pattern of Leptobrachella in Doi Inthanon deserves further study. As Thailand’s highest mountain and biodiversity reservoir, the need for further biological exploration is urgent given ongoing habitat loss and degradation.